Guinea: Recent developments in agricultural research - Stads, Gert-Jan; Béavogui, Famoï; Diawara, Sékou (International Food Policy Research Institute, 2010)
Since the early 1980s, Guinea's agricultural research and development (R&D) has been marked by contracting expenditures, whereas its human resource capacity has remained more or less unchanged. In 2008, the country employed 229 full-time equivalent (FTE) agricultural researchers, and public agricultural R&D expenditures totaled 3.9 billion Guinean francs or 3.2 million PPP dollars (both in constant 2005 prices), which is well below the levels recorded in the 1980s. Unless otherwise stated, all prices in this note are based on purchasing power parity (PPP) exchange rates, which relect the purchasing power of currencies more efectively than do standard exchange rates because they compare the prices of a broader range of local-as opposed to internationally traded-goods and services.